2007
DOI: 10.1016/j.trsl.2006.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacies of 2 cysteine prodrugs and a glutathione delivery agent in a colitis model

Abstract: Oxidant-mediated injury plays an important role in the pathophysiology of inflammatory bowel disease (IBD). Recently, antioxidants were shown to modulate colitis in mice. In this study, the protective effects of L-cysteine and glutathione (GSH) prodrugs are further evaluated against progression of colitis in a murine model. ICR mice were fed compounds incorporated into chow as follows: Group (A) received chow supplemented with vehicle. Group (B) was provided 2-(RS)-npropylthiazolidine-4(R)-carboxylic-acid (PTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 27 publications
2
68
0
Order By: Relevance
“…Opn expression is up-regulated in peripheral blood and intestinal mucosa of patients (24)(25)(26)(27)(28)(29) and mice with IBD (14,15,27,30). We found that Opn protein and mRNA (Spp1) levels were also significantly higher in MLN cells (MLNCs) from mice with acute colitis (∼fourfold and ∼46-fold, respectively) compared with healthy mice (Fig.…”
Section: Significancementioning
confidence: 77%
See 1 more Smart Citation
“…Opn expression is up-regulated in peripheral blood and intestinal mucosa of patients (24)(25)(26)(27)(28)(29) and mice with IBD (14,15,27,30). We found that Opn protein and mRNA (Spp1) levels were also significantly higher in MLN cells (MLNCs) from mice with acute colitis (∼fourfold and ∼46-fold, respectively) compared with healthy mice (Fig.…”
Section: Significancementioning
confidence: 77%
“…Opn is expressed by DCs and other immune cell types, such as lymphocytes, during autoimmune responses (16)(17)(18)(19)(20)(21)(22), and its expression by DCs during autoimmunity contributes to disease severity (17-19, 21, 23). In addition, Opn expression is highly up-regulated in intestinal immune and nonimmune cells and in the plasma of patients with CD and UC (24)(25)(26)(27)(28)(29), as well as in the colon and plasma of mice with experimental colitis (14,15,27,30). Increased plasma Opn levels are related to the severity of CD inflammation (29), and certain Opn gene (Spp1) haplotypes are modifiers of CD susceptibility (31), indicating that Opn could be used as an IBD biomarker (27).…”
mentioning
confidence: 99%
“…Cysteine has been reported to show anti-inflammatory effects (14). Drugs that contain cysteine have been used to cure intestinal inflammation and have created promising outcomes (13). In a recent study, the free amino acid form, L-cysteine, was deployed against inflammatory bowel disease (37).…”
Section: Discussionmentioning
confidence: 99%
“…For example, proteins that include sulfhydryl groups and glutathione are accepted as endogenous anti-inflammatory mediators against the reactive oxygen species produced by activation of NADPH oxidase within polymorph nuclear neutrophils in inflammation and tissue damage (13). Thiol antioxidants such as glutathione and N-acetylcysteine inhibit cytokine production (14).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these findings, several researchers described animal models that can mimic the OPN-induced colitis in vivo as well as block OPN-induced inflammation [20][21][22][23].…”
mentioning
confidence: 99%